Model Kepemimpinan Kepala Sekolah Dalam Meningkatan Mutu Pendidikan di Madrasah Ibtidaiyah - Amalia, Renasa; Siahaan, Dina Nadira Amalia (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the leadership model of school principals in improving the quality of education at MIS Al-Washliyah Labuhanbatu Utara. Using a qualitative approach with a case study design, the research collects data through observations, interviews with the principal, teachers, and staff, as well as document analysis. The findings reveal that the principal applies a combination of transformational and participative leadership models. Transformational leadership motivates teachers and staff, while participative leadership involves all stakeholders in decision-making. However, challenges such as limited resources, slow cultural change, and lack of parental support hinder the full implementation of these leadership models. Despite these obstacles, the principal continues to foster a supportive and collaborative environment for educational improvement. This study contributes to the literature on leadership in religious-based education, offering valuable insights for school managers in implementing effective leadership models to enhance educational quality.